AN OVERVIEW OF NUCLEAR POWER ECONOMICS AND SAFETY ISSUES IN THE WORLD AND IN PAKISTAN - Ahmad, S. A.; Hayat, T.; Mahmood, A. (The Nucleus, 2020)
Nuclear Power generation has been and is a serious option in the energy basket for economic competitiveness as well as energy autarky and security. However, two most important factors, i.e. economics and safety, need to be discussed from the developing markets point of view while watching global trends. The type, size and vendor information is presented in a manner that economic and safety paradigm is more clearly visible. Most of the 12,000 reactor-years operation experience in the world is obtained from generation I & II Nuclear Power Plants, and it is considered that they are still relevant in most energy markets. Currently, like countries such as the USA, UK and others, Pakistan has Generation II NPP technology, so both economics and safety conditions may not change in the near future. However, alternative data is presented to provide a better understanding; and its relevance to Pakistan is stressed.